Analisis Distribusi Asap Dampak Kebakaran Hutan dan Lahan di Provinsi Jambi - Fauziah, Annisa; Zuhdi, Mocd; Syarifuddin, Hutwan (Jurnal Pembangunan Berkelanjutan, 2023)
Forest and land fires are one of the hydrometeorological disasters that occur every year, especially during the dry season in Jambi Province. One of the impacts caused by forest and land fires is air pollution in the form of smoke which disrupts various sectors including health and transportation. Identification of smoke distribution due to forest and land fires can be done using remote sensing, namely using Himawari-8 satellite imagery with the RGB (red green blue) method. Smoke distribution modeling can also be done using the AERMOD software. The results of identifying the distribution of smoke in Jambi Province using Himawari-8 satellite imagery in 2015 and 2019 show that the center of the fire originated from Muaro Jambi Regency with the direction of movement of smoke from Southeast to Northwest. Modeling smoke distribution with AERMOD shows the same results as satellite imagery, where the smoke distribution moves from the Southeast to the Northwest with the highest emission intensity 1 hour after emissions are produced by smoke from fires.